CONSERVATION METHODS FOR NATIVE FRUIT SEEDS - Pirola, Kelli; Dotto, Marcelo; Cassol, Darcieli Aparecida; JÃºnior, AmÃ©rico Wagner; Possenti, Jean Carlo; Citadin, Idemir (REVISTA DE AGRICULTURA, 2017)
The objective of this study was to establish conservation techniques for native fruit seeds. There were used seeds of guabijzeiro, pitangueira, jabuticabeira de cabinho and cerejeira-do-mato, divided into two lots, being applied cassava starch biofilms (6%) and without the use of it. After, the seeds were divided into two lots, one for conservation in bottles of polyethylene terephthalate (PET) and other in waxed paper bag and stored for 18 periods up to 360 days until sowing. The experimental design was completely randomized blocks, in factorial 2 x 2 x 18 (storage packaging x biofilm x storage time), with 4 replications of one hundred seeds by plot. After 60 days of the beginning of experiment, the germination (%) and emergence speed index (ESI) were evaluated. The PET bottle permitted greater conservation as increased the seed germination. The biofilm can be considered a promising technique to increase germination efficiency of cerejeira-da-mata.